Analisis Kesuburan Tanah di Pertambangan Minyak Tradisional Desa Wonocolo Kecamatan Kedewan, Kabupaten Bojonegoro: Analysis of Soil Fertility in Traditional Oil Mining in Wonocolo Village, Kedewan District, Bojonegoro Regency - Nindy Callista Elvania; Yenny Sri Margianti; Santi Amanda Tiara; Dimas Bagus Nugroho (Media Ilmiah Teknik Lingkungan (MITL), 2023)
Wonocolo Village is known as a traditional mining area. This study aims to determine the level of soil contamination in traditional oil mining activities by testing N, P, K, organic matter and lime content of the soil. The method used in this research is using a proposive random sampling method. The results of testing the quality of soil in mining activities were found not to contain N,P,K. This can be seen when testing using N,P,K solutions, there was no change in soil color, organic matter and soil lime content when testing on 7 soil samples. only 2 soil samples contained organic matter and soil lime content, namely the 3rd and 7th samples. This can be seen from the presence of foam on the soil samples when dripped with H2O2 and HCL solutions. So it can be concluded that the soil in the Wonocolo mining area is highly polluted, so it is necessary to carry out bioremediation and phytoremediation the quality of soil in mining activities were found not to contain N,P,K. This can be seen when testing using N,P,K solutions, there was no change in soil color, organic matter and soil lime content when testing on 7 soil samples. only 2 soil samples contained organic matter and soil lime content, namely the 3rd and 7th samples. This can be seen from the presence of foam on the soil samples when dripped with H2O2 and HCL solutions. So it can be concluded that the soil in the Wonocolo mining area is highly polluted, so it is necessary to carry out bioremediation and phytoremediation.